“Relación entre el nivel de conocimiente,actitudes y prácticas sobre el examen de papanicolaou en mujeres en edad fértil sexualmente activas de la urbanización “Las Palmeras” en el Distrito de Morales, Julio – Diciembre 2011” - Carrasco Saavedra, Juan Ramón (2011)
The present study aimed to determine the relationship between the level of knowledge, attitudes and practices regarding the Pap test with childbearingage women sexually active in the urbanization "Las Palmeras" in the district of Morales, July-December 2011. Quantitative research was conducted, correlational descriptive, prospective, cross sectional study. Surveys were conducted by structured interview technique to a total of 111 sexually active MEF. For processing and analysis of information, we designad a database in Excel and SPSS 2.011 17. We used descriptiva statistics such as frequency, percentage, arithmetic mean and standard deviation. lnferential statistics to determine relationships between variables using chi-square test with a significance level <0.05. Women of childbearing age are sexually active in the urbanization "Las Palmeras" Morales district are characterized by: 42.34% between 20 and 29 years, the 61.26% are cohabiting, the 44.14% are secondary level. Also, 60.36% knew that the Pap is used for the detection of cervical cancer, 43.24% know that the first sexual intercourse is the most important indicator for the exam and Pap test. Similarly, the 50.45% had a high level of knowledge about the Pap test, 54.05% showed a favorable attitude to the Pap test, 76.58% adopt an appropriate practice in front of the Pap test. Another key finding shows that there is a statistically significant relationship between the level of high knowledge and positiva attitude, and between the high level of knowledge and the proper practica of the MEF versus Pap test (p <0.05), and there statistically significant relationship between positiva attitude and the proper practice of the Pap test (p <0.05). Keywords: cervical cancer, Pap, knowledge, attitude, practica.